Challenges of collborataive blend learning in undergraduate students - Monteiro, Elisa; Morrison, Keith (Education Research and Evaluation, 2014)

Complexity theory and curriculum reforms in Hong Kong - Morrison, Keith (Pedagogy, Culture & Society, 2003)

Complexity Theory, School Leadership and Management: Questions for Theory and Practice - Morrison, Keith (Educational Management Administration & Leadership, 2010)
Complexity theory (CT) has had a meteoric rise in management literature and the social sciences. Its fledgling importation into school leadership and management raises several questions and concerns. This article takes one view of CT and argues that, though its key elements have much to offer school leadership and management, caution has to be exercised in accepting CT too readily, as it: (1) is unclear on its own novelty, nature and status; (2) can be regarded as disguised ideology in conflating description and prescription; (3) confuses explanation with prediction; (4) is relativist, undermining its own status; (5) contains problems in its advocacy of self-organization; (6) neglects the ethical and emotional dimensions of leadership and management; and (7) risks exonerating school leaders and managers from reasonable expectations of accountability and responsibility. The article concludes that there are questions to CT at the levels of theory, ontology, deontology and ethics, but that it offers useful challenges for school leadership and management.

Conceptual replications, research, and the “what works” agenda in education - Morrison, Keith (Educational Research and Evaluation, 2022)

Does repeating a year improve performance? The case of teaching English - Morrison, Keith; Ieong On No, Anna (Educational Studies, 2007)

Educational Philosophy and the Challenge of Complexity Theory - Morrison, Keith (Educational Philosophy and Theory, 2008)

Group work and cultural characteristics in a Chinese school - Morrison, Keith; Garcia, Alejandro Salcedo; Wong, Sin Teng (Educational Research and Evaluation, 2020)

Ideology, Linguistic Capital and the Medium of Instruction in Hong Kong - Morrison, Keith; Lui, Icy (Journal of Multilingual and Multicultural Development, 2000)

Improving Teaching and Learning in Higher Education: Metaphors and Models for Partnership Consultancy - Morrison, Keith (Evaluation & Research in Education, 2003)

Interviewing children in uncomfortable settings: 10 lessons for effective practice - Morrison, Keith (Educational Studies, 2013)

Leadership for self-organisation: complexity theory and communicative action - Morrison, Keith (International Journal of Complexity in Leadership and Management, 2011)

Lone parents' experiences as higher education students: learning to juggle - Morrison, Keith (Educational Research and Evaluation, 2013)

Measuring and Targeting Internal Conditions for School Effectiveness in the Free State of South Africa - Kgaile, Abraham; Morrison, Keith (Educational Management Administration & Leadership, 2006)
A questionnaire-based methodology for constructing an overall index of school effectiveness is reported, focusing on within-school conditions of schools, which is currently being used in the Free State of South Africa. The article reports the construction and use of a straightforward instrument for measuring the effectiveness of key aspects of the conditions for school effectiveness in the Free State, using a variety of dimensions. It indicates how this instrument can identify where to intervene in improving schools in order to gain the maximum return on investment of time, effort, development activity and support. The instrument provides aggregated and disaggregated data for individual schools, groups of schools and whole districts, both at a single point in time and over time, thereby enabling the most economical and beneficial development to be planned for targeted individual schools and groups of schools. It enables users to identify the key drivers of the internal school conditions for effectiveness, development and change in schools.

Men and women in employment in Macau: A longitudinal survey of inequality. - Morrison, Keith (Journal of Macau University of Science and Technology, 2009)

Methods, understandings, and expressions of causality in educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Online and paper evaluations of courses: a literature review and case study - Morrison, Keith (Educational Research and Evaluation, 2013)

Paradox Lost: Toward a Robust Test of the Chinese Learner - Morrison, Keith (Education Journal, 2006)
This article suggests that attempts to date to unravel the paradox of the Chinese learner are incomplete and inadequately modeled, and that the complexities of the paradox have not yet been fittingly operationalized or alternative explanations of research data investigated. It contends that attempts either to state or to unravel the paradox are chimerical, as they risk oversimplifying a complex phenomenon, the extent and nature of which are insufficiently understood to date. The article argues that investigating the phenomenon of Chinese learners' strong performance in international measures of achievement requires researchers to operate more rigorously in their search for alternative and multiple explanations of results in terms of causality, sampling, and representing heterogeneity. Several explanations of data on the paradox are presented, and alternative explanations which might be more usefully explored are provided. The article also questions the extent to which research on the Chinese learner, with a search for a unitary set of characteristics, is not, itself, prey to totalizing, collectivist ideologies cast in unrealistic meta-narratives. Recommendations are made for further research.

Pedagogy in higher education - Morrison, Keith (Chinese Cross Currents, 2005)

Randomised Controlled Trials for Evidence-based Education: Some Problems in Judging 'What Works' - Morrison, Keith (Evaluation & Research in Education, 2001)

Realizing the promises of replication studies in education - Morrison, Keith (Educational Research and Evaluation, 2019)

Review of Biesta. G. (2020) Educational research: an unorthodox introduction, Educational Research and Evaluation - Morrison, Keith (Educational Research and Evaluation, 2020)

Review of Gorard, S. (2020) Getting evidence into education: evaluating the routes to policy and practice - Morrison, Keith (Educational Research and Evaluation, 2020)

School inspection in small states and territories: an overview and case study of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2009)

Searching for causality in the wrong places - Morrison, Keith (International Journal of Social Research Methodology, 2012)

Sensitive educational research in small states and territories: the case of Macau - Morrison, Keith (Compare: A Journal of Comparative and International Education, 2006)

Simplicity and Complexity in Contemporary School Leadership: A Response to Grace - Morrison, Keith (British Journal of Educational Studies, 2001)

Structuration theory, habitus and complexity theory: elective affinities or old wine in new bottles? - Morrison, Keith (British Journal of Sociology of Education, 2005)

Testing to Destruction: A problem in a small state - Morrison, Keith; Joan, Tang Fun Hei (Assessment in Education: Principles, Policy & Practice, 2002)

The academic and intellectual life of Macau - Morrison, Keith (Review of Culture (Revista de Cultura), 2014)

The Colonization of Lifeworlds of Education by Work: Restoration and Recoupling of Lifeworld and System in the Inner Self - Morrison, Keith (Horizons of Education, 2015)
The argument is raised that, in an age of the networked, connected society in an information-rich environment with communication possibilities as never before experienced or made possible, the displacement of educational virtues of morality, ethics and the development of all-round human beings, by those of money, labour, power and work are speeding apace, and the disconnect between system and lifeworld is increasing. Drawing initially on the work of Habermas, in which the colonization of the lifeworld occurs by system imperatives of rationalization, labour, money and power, the paper argues that such moves are manifested starkly in discourses of the relation between education and work, and five areas are introduced in which the links operate. The marketization and commodification of education, together with its incorporation into the service of capital and labour, are attested through a short worked example of one small territory within the larger context of China. Then, taking a lead from Sertillanges and Habermas’s later work, the paper argues for: (a) a reaffirmation of the importance of moral, ethical and spiritual dimensions of education; (b) the breaking of a narrowly instrumental, capital-acquisitive view of education as serving the jobs market and social control and towards a liberating view of education as communicative action and the development of being rather than simply behaving; (c) the importance of transcendence and immanence; and, thereby, (d) moves towards the re-integration of system and lifeworld in participating subjects.

The poverty of curriculum theory: a critique of Wraga and Hlebowitsh - Morrison, Keith R. B. (Journal of Curriculum Studies, 2004)

The scalpel model of educational research - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

The truth, the whole truth, and nothing but the truth - Morrison, Keith; van der Werf, Greetje (Educational Research and Evaluation, 2020)

Toward an educational agenda for Macau at the start of the new millennium - Morrison, Keith (China Perspectives, 2003)

Undergraduate students in part‐time employment in China - Tam Oi I, Betty; Morrison, Keith (Educational Studies, 2005)